The Use of Gamification-Based Duolingo Application in Increasing Student Motivation is Reviewed From the Theory of Self-Determination - Muttaqin, Mirza; Zuhdi, Halimi; Ridwan, Ridwan (Faculty of Islamic Sciences, Raden Rahmat Islamic University Malang, 2025)
This study aims to evaluate the extent to which the gamification-based Duolingo application can increase students' motivation in learning Arabic, especially in vocabulary mastery or mufrodat, with the Self-Determination Theory (SDT) theoretical approach. SDT focuses on the importance of intrinsic motivation, which is driven by three main aspects: autonomy or independence, competence or ability, and interconnectedness or relationships that are established in the context of learning. This study uses a quantitative approach with a Descriptive Survey design to provide a more real picture of the influence of the use of this application on student motivation. Data collection was carried out with an SDT questionnaire instrument that measured the level of student motivation through the three main components. The results of the data analysis showed a significant increase in motivation among students who participated in the experiment. These findings indicate that the gamification-based Duolingo application plays a role in increasing students' intrinsic motivation in learning mufrodat, especially by strengthening a sense of independence, improving perceived abilities, and creating a sense of connectedness or relevance in the learning process. Gamification-based Duolingo has great potential as an effective tool in language learning, especially in helping to increase students' motivation to master new vocabulary. It is evidenced by the questionnaire data which got a score of 88%. Keywords: Duolingo, gamification, Self-Determination Theory, mufrodat